The effect of internal and external visualization of rotation on postural stability - Jost, Leonardo; Siebertz, Markus; Hofmann, Philipp; Jansen, Petra (Frontiers in Cognition, 2024)
During mental rotation tasks, it is assumed that participants visualize a rotation of objects in their minds (internal visualization), but mental rotation has also been linked to the visible rotation of objects on a screen (external visualization). The angular disparity in mental rotation also influences postural sway, the movements of the body center. Postural sway is thus suspected as one type of indirect measurement of the rotation process. We compare the external visualization of rotation with the suspected internal visualization during mental rotation tasks. We suspect both are similar and thus produce a comparable effect on postural sway. 150 Participants completed three rotation tasks with cube figures, two of which were aided by external visualization. Their center of pressure was measured throughout. The effects of external visualization, angular disparity, and their interaction on postural sway were compared using Bayesian statistics and a decision boundary of 3 or 1/3.The results indicate no differences between conditions for all postural sway parameters. We observe differences between conditions in cognitive load and reaction time. However, as these partially also differ between the two external visualization conditions and do not transfer to differences between the postural sway parameters, the underlying processes in the three conditions are likely similar.Our results support the notion that the visualization of rotation is central to postural sway during mental rotation. This further supports that the rotation process of the external visualization and mental rotation are similar and thus that stimuli are indeed rotated mentally during mental rotation tasks. Our results further support that the common process between mental and manual rotation lies in the visualization instead of mental rotation being an imagined motor action. Because visual control and feedback play an essential role in many motor tasks, the results could also be of further interest for a more general link between motor and cognitive tasks and bidirectional benefits through the construction of visual similarities.